The response of human macrophages to 3D printed titanium antibacterial implants does not affect the osteogenic differentiation of hMSCs - Garmendia Urdalleta, Amaia; Van Poll, Mathijs; Fahy, Niamh; Witte-Bouma, Janneke; Van Wamel, Willem; Apachitei, Iulian; Zadpoor, Amir A.; Fratila-Apachitei, Lidy E.; Farrell, Eric (Frontiers in Bioengineering and Biotechnology, 2023)
Macrophage responses following the implantation of orthopaedic implants are essential for successful implant integration in the body, partly through intimate crosstalk with human marrow stromal cells (hMSCs) in the process of new bone formation. Additive manufacturing (AM) and plasma electrolytic oxidation (PEO) in the presence of silver nanoparticles (AgNPs) are promising techniques to achieve multifunctional titanium implants. Their osteoimmunomodulatory properties are, however, not yet fully investigated. Here, we studied the effects of implants with AgNPs on human macrophages and the crosstalk between hMSCs and human macrophages when co-cultured in vitro with biofunctionalised AM Ti6Al4V implants. A concentration of 0.3 g/L AgNPs in the PEO electrolyte was found to be optimal for both macrophage viability and inhibition of bacteria growth. These specimens also caused a decrease of the macrophage tissue repair related factor C-C Motif Chemokine Ligand 18 (CCL18). Nevertheless, co-cultured hMSCs could osteogenically differentiate without any adverse effects caused by the presence of macrophages that were previously exposed to the PEO (± AgNPs) surfaces. Further evaluation of these promising implants in a bony in vivo environment with and without infection is highly recommended to prove their potential for clinical use.